Idea of Remoteness in The Collector by John Fowles and The Tempest by William Shakespeare - Kanitrová, Alice (Univerzita Pardubice, 2013)
This bachelor thesis deals with the ideas of remoteness, isolation, and seclusion in the works The Collector by John Fowles and The Tempest by William Shakespeare. An analysis of the idea of remoteness from various perspectives is conducted in the practical part and is based on relevant secondary literature. The most significant aspect of remoteness is though the theme of an island; characteristics of which are present in both works The Tempest as well as The Collector. On the grounds of my findings are therefore discussed the means how John Fowles uses the play by William Shakespeare with the aspects of remoteness, isolation, and seclusion in mind.
Aspekt vzdálenosti v dílech The Collector a The Tempest
Keywords: odlehlost; osamocení; izolace; ostrov; Tempest; Collector; remoteness; seclusion; isolation; island